Traumatic Axonal Injury in the Optic Nerve: Evidence for Axonal Swelling, Disconnection, Dieback, and Reorganization - Wang, Jiaqiong (Mary Ann Liebert, Inc., 2011)
Traumatic axonal injury (TAI) is a major feature of traumatic brain injury (TBI) and is associated with much of its morbidity. To date, significant insight has been gained into the initiating pathogenesis of TAI. However, the nature of TAI within the injured brain precludes the consistent evaluation of its specific anterograde and retrograde sequelae. To overcome this limitation, we used the relatively organized optic nerve in a central fluid percussion injury (cFPI) model. To improve the visualization of TAI, we utilized mice expressing yellow fluorescent protein (YFP) in their visual pathways. Through this approach, we consistently generated TAI in the optic nerve and qualitatively and quantitatively evaluated its progression over a 48-h period in YFP axons via confocal microscopy and electron microscopy. In this model, delayed axonal swelling with subsequent disconnection were the norm, together with the fact that once disconnected, both the proximal and distal axonal segments revealed significant dieback, with the proximal swellings showing regression and reorganization, while the distal swellings persisted, although showing signs of impending degeneration. When antibodies targeting the C-terminus of amyloid precursor protein (APP), a routine marker of TAI were employed, they mapped exclusively to the proximal axonal segments without distal targeting, regardless of the survival time. Concomitant with this evolving axonal pathology, focal YFP fluorescence quenching occurred and mapped precisely to immunoreactive loci positive for Texas-Red-conjugated-IgG, indicating that blood–brain barrier disruption and its attendant edema contributed to this phenomenon. This was confirmed through the use of antibodies targeting endogenous YFP, which demonstrated the retention of intact immunoreactive axons despite YFP fluorescence quenching. Collectively, the results of this study within the injured optic nerve provide unprecedented insight into the evolving pathobiology associated with TAI.